REVIEW AND COMPARISON OF TRAFFIC CALMING SOLUTIONS: MEXICO CITY AND KATOWICE - Delia Berenice VILLARREAL CHÁVEZ; Agata KUREK; Grzegorz SIERPIŃSKI; Jakub JUŻYNIEC; Bartosz KIELC (Scientific Journal of Silesian University of Technology. Series Transport)
The article addresses solutions implemented in two cities, namely,Mexico City and Katowice, with the aim of improving road traffic safety. Despite the distance of more than 10,000 km separating the two cities, a comparison revealed many similar solutions having been implemented in both of them. This comparative case study is complemented with a collation of statistics pertaining to accidents, fatalities and injured persons as reported in the period 2012-2015.